Economic Problems of Exploring Hydrocarbons in Russian Northern Provinces in the Context of International Interests - Larchenko, Lyubov Vasilievna; Kolesnikov, Roman Aleksandrovich; Tumanova, Galina Pavlovna; Kibenko, Valeriy Aleksandrovich (International Journal of Energy Economics and Policy, 2016)
The goal of the article is to analyze the present state and perspectives of exploring gas and oil resources of the Russian North in the context of economic interests of a number of foreign countries, to reveal both common things in interests of the both parties, and inconsistencies that must be aligned. The methodology of the research is based on the system approach to estimating the state of gas and oil resources of the Russian North and comprehensive analysis of aligning economic interests of Russia and a number of foreign countries. A complex of general scientific and special methods of research was used, including abstract-logical, balance, statistical analysis and others. The article shows that the Russian North is extremely rich in gas and oil resources that are both currently exploited and promising for reclaiming especially on the shelf of Arctic seas. It analyzes reasons of the decrease in the gas and oil production in the country that has occurred over recent years. It is caused by the fall of the demand for hydrocarbons in the world, sectoral sanctions, and the decrease in the production of the mineral resources base. Gas and oil resources of Russia fall within the interests of a number of foreign countries, mainly West European countries for which stable provision of the economy with raw hydrocarbons becomes one of the most important strategic tasks. Long-term economic interests of Russia coincide with the interests of the European Union, however, not fully. The authors come to the conclusion that in case of supplying hydrocarbons economic interests of Russia and European Union countries must be aligned not only in terms of searching for mutually profitable forms of cooperation but also solving basic inconsistencies that lie in the basis of opinions discrepancies. Keywords: gas and oil resources, the Russian North, Arctic shelf, Western European countries, Asia-Pacific countries, alignment of interests. JEL Classifications:, D74, F00, L71, Q32, Q34